An investigation on organic Rankine cycle incorporating a ground-cooled condenser: Working fluid selection and regeneration. (15th June 2022) - Mahmoud, Montaser; Alkhedher, Mohammad; Ramadan, Mohamad; Naher, Sumsun; Pullen, Keith
Abstract: This research presents an optimization of a power generation system incorporating a ground-cooled condenser. It focuses on the mitigation of the adverse effects of critical parameters such as low mass flow rates and large ground loops. This includes an investigation of different configurations (basic and regenerative cycles) and working fluids to ascertain their effects on the performance of the system. Three refrigerants, R123, R124 and R245fa, were compared in terms of working fluid's performance. The purpose of the system optimization is to increase the net output power whilst reducing the capital cost of installation. At an inlet expander pressure of 3 MPa, as the condensation temperature was decreased from 25 °C to 15 °C the enhancements in net output power were 7.35%, 12.13% and 8.77% for R123, R124 and R245fa, respectively in the case of basic organic Rankine cycle. However, the highest performance in terms of net output power was recorded for R123 in both configurations under the investigated conditions. Based on the calculations of net output power and heat rejection, the regenerative cycle is highly recommended since it provides significant increase in the output power without considerably changing the amount of heat rejected to the ground.